Factors associated with autism severity among Malaysian children with Autism Spectrum Disorder - Eow, Shiang Yen; Gan, Wan Ying; Lim, Poh Ying; Awang, Hamidin; Mohd Shariff, Zalilah (Elsevier, 2020)
Background: Children with Autism Spectrum Disorder (ASD) of different levels of symptom severity may exhibit a wide range of behaviours and characteristics. There is a limited nutrition-related study on children with ASD of different severity in Malaysia. Aims: This cross-sectional study aims to determine the association between sociodemographic factors, parental factors, and lifestyle factors with autism severity in children with ASD. Methods and procedures: A total of 224 children with ASD were included in this study. Their mothers completed a self-administered questionnaire on sociodemographic characteristics, autism severity, parenting style, parental feeding practices, parenting stress, child's sleep habits and eating behaviours. Outcomes and results: As high as 78.1 % of the children with ASD demonstrated a high level of autism severity. Multiple linear regression showed that father's employment status (B = 6.970, 95 % CI = 3.172, 10.768, p < 0.001) and perceived child weight (B = 3.338, 95 % CI = 1.350, 5.327, p = 0.001) predicted autism severity. Conclusions and implications: Children with ASD in this study had a high level of autism severity. Regular anthropometric measurements by healthcare professionals should be conducted at the autism intervention centres. It is important to have multidisciplinary collaboration in future research to develop customised guidelines for parents with autistic children.